Vision to action for agroecological transitions in the living landscapes: India progress report - Singh, Sonali; Gupta, Shweta; Kumar, Gopal; Maliappan, Sudarshan; Alvi, Muzna; Krishnan, Smitha; Sikka, Alok (CGIAR System Organization, 2024)
The One CGIAR Agroecology initiative aims to contribute to achieving agroecological transition (AET) in eight countries through developing and scaling a range of innovations by using a participatory action-research approach involving the key stakeholders of the Agroecological Living Landscapes (ALLs) in multi-stakeholder territorial spaces in each country. It does so by jointly developing a shared vision, behaviour change, behaviour drivers and shared action plan with key stakeholders. Once the action plan is set to achieve the vision, transition pathways towards achieving them become the core of the underlying innovation process. The process entails inclusiveness, representativeness, interest, and motivation of the stakeholders to contribute to AET and ensure shared action plan and goals are demand driven.